Overexpression of the homoterpene synthase gene, OsCYP92C21, increases emissions of volatiles mediating tritrophic interactions in rice. (29th December 2020) - Li, Wei; Wang, Lingnan; Zhou, Fei; Li, Changyan; Ma, Weihua; Chen, Hao; Wang, Guirong; Pickett, John A.; Zhou, Jing‐Jiang; Lin, Yongjun
Abstract: Plant defence homoterpenes can be used to attract pest natural enemies. However, the biosynthetic pathway of homoterpenes is still unknown in rice, and the practical application of such indirect defence systems suffers from inherent limitations due to their low emissions from plants. Here, we demonstrated that the protein OsCYP92C21 is responsible for homoterpene biosynthesis in rice. We also revealed that the ability of rice to produce homoterpenes is dependent on the subcellular precursor pools. By increasing the precursor pools through specifically subcellular targeting expression, genetic transformation and genetic introgression, we significantly enhanced homoterpene biosynthesis in rice. The final introgressed GM rice plants exhibited higher homoterpene emissions than the wild type rice and the highest homoterpene emission reported so far for such GM plants even without the induction of herbivore attack. As a result, these GM rice plants demonstrated strong attractiveness to the parasitic wasp Cotesia chilonis . This study discovered the homoterpene biosynthesis pathway in rice, and lays the foundation for the utilisation of plant indirect defence mechanism in the "push‐pull" strategy of integrated pest management through increasing precursor pools in the subcellular compartments and overexpressing homoterpene synthase by genetic transformation. Abstract : This study characterizes first rice homoterpene biosynthesis gene OsCYP92C21 . The results demonstrate the homoterpene emission is dependent on the precursor pools and can be significantly enhanced without any induction through subcellular targeting gene expression and genetic introgression.